A STUDY ON THE SPEAKING ABILITY OF THE SECOND YEAR STUDENTS OF SMPIT AT-TAQWA PELALAWAN - Najiya, Liya; Eliwarti, Eliwarti; Mahdum, Mahdum (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This descriptive research was conducted to find out the students’ speaking ability in term of recount text. The samples of this research were 40 students from SMPIT At-Taqwa Pelalawan. The researcher used cluster random sampling technique to choose the samples. The instrument to measure the students’ speaking ability was in the form of monologue, retelling a story in recount text. The students’ speaking scores were measured by three raters. Based on the data analysis, it can be concluded that the mean score of the students’ speaking ability is 53. From each aspect, it could be seen that the highest score was in terms of vocabulary with the average score of 64. It is followed by grammar with the average score of 60, then comprehension with the average score of 57.5, and fluency with the average score of 49. The lowest score was in terms of pronunciation with the average score of 46.3. Therefore, it was recommended for the teacher to provide more speaking activities which support students’ speaking skill, particularly in terms of pronunciation and fluency, since these aspects are the lowest, and the students’ need to practice their speaking skill inside and outside the classroom.Key Words: Speaking, Ability, Speaking Ability